The nexus between building information modelling implementation strategies, adoption, and levels of construction supply chain integration in South Africa - Olugboyega, Oluseye (Department of Construction Economics and Management, 2021)
The adoption of Building Information Modelling (BIM) on construction projects is not widespread yet, because there is a growing albeit slow uptake. There is no strategically structured BIM adoption guide available on construction projects for ensuring integration and collaboration among the Building Information Modelling- Supply Chain Members (BIMSCM). Scholars adduce the lack of adoption of BIM on construction projects to the use of ineffective BIM implementation strategies. Therefore, this research investigated BIM adoption and the current dominant BIM implementation strategies used in the South African construction industry. It also examined whether BIM implementation strategies and BIM adoption on construction projects impact on the occurrence of integration and collaboration among the BIM-SCM in the South African construction industry. Using modified Implementation Process Theory, the research collected primary data using a mixed-methods research approach that involved the collection of both qualitative and quantitative data from 872 respondents randomly selected from the 1,871 BIM-based construction projects' direct participants who indicated their willingness and availability to participate in the research from the cidb databse of construction professionals in South Africa. The qualitative data collected with respect to barriers to BIM adoption and dominant BIM implementation strategies were analysed using thematic analysis. The quantitative data collected with respect to BIM adoption, barriers to BIM adoption, integration and collaboration, and BIM implementation strategies were analysed using Mean Item Score (MIS), Confirmatory Factor Analysis (CFA), and Structural Equation Modelling (SEM).The SEM method used was the Maximum Likelihood Estimation. Before modelling process, CFA was used to confirm the validity and reliability of the quantitative data using the Factor Loading, Eigenvalue, correlation coefficient, Kaiser-Meyer-Olkin (KMO) value, Bartlett's test results, and Average Variance Explained (AVE). It emerged that the possibility of getting high-value clients, quest for a competitive edge, need for technological sophistication, need to be socially acceptable to the clients, incorporation of BIM adoption into the vision of the organisations, and development of BIM capabilities as new values in their organisations are the dominant BIM implementation strategies used in the South African construction industry. The findings also revealed that the dominant BIM implementation strategies are private driven and are not bringing about an adequate reduction in the BIM adoption barriers. Investigation of the evidence of the application of BIM tools and processes with respect to the adoption of BIM on construction projects showed that fewer building information models were developed for projects, BIM performance assessment was not intensive, emphasis was not placed on the level of objects' clarity of building information models, BIM skills and competencies were insufficient, and BIM management was dis-organised. The parameter estimates from the SEM analysis of the interactions between the BIM implementation stages indicated that the success of the BIM implementation process in South Africa depends on a positive interplay between the interacting implementation stages. The parameter estimates from the SEM analysis of the interaction between the BIM implementation stages also revealed that BIM implementation strategies control the impacts of a reduction in BIM adoption barriers on the extent of BIM adoption. However, the findings revealed that the BIM implementation strategies currently in use did not possess the required forces and intensity to strengthen the positive interplay between the interacting BIM implementation stages. The study concluded that the essential BIM implementation strategies are not in use in South Africa, while the BIM implementation strategies currently in use are not appropriately and effectively employed. However, there is evidence of elementary BIM adoption on projects and low occurrence of integration and collaboration among the BIM-SCM in South Africa. The lack of adequate skills and experience of BIM management and the inadequate understanding of what BIM adoption on projects entails mean that working policies and legislation on BIM adoption are required to drive a successful BIM implementation process. This research provides new insights on the structures and stages of the BIM implementation process and postulations that will aid the comprehension of the interconnections between BIM implementation strategies and BIM adoption on construction projects in South Africa. More importantly, this research has extended the existing theories on BIM adoption and the interactions between the levels of BIM adoption on construction projects and collaboration among the BIM-SCM.